Hipérboles del deseo en el discurso publicitario: nota sobre el caso Breil - Canga Sosa, Manuel (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2008)
This paper deals with the influence of the human desire in the staging of some commercials and posters designed by the Italian company Breil from mid 90’s until today. The analysis of these advertising texts throws light on the nature and function of the image in the general context of contemporary advertising. The image is able to create a direct visual incentive through the use of sexual motifs and situations. It can also contribute to magnify the product´s image and to raise its status in case the references used are correctly elaborated.